Pancreas, kidney and skin regeneration - Pham, Phuc Van (Stem cells in clinical applications,, 2017)
This invaluable resource discusses clinical applications with effects and side-effects of applications of stem cells in diabetes, kidney and wound treatment. All chapters are contributed by pre-eminent scientists in the field and covers such topics as stem cells and cell therapy in the treatment of diabetes mellitus, kidney failure, wound and other skin aging diseases, characteristics of some kinds of stem/progenitor cells for therapy, future directions of the discussed therapies and much more. Pancreas, Kidney and Skin Regeneration and the other books in the Stem Cells in Clinical Applications series will be invaluable to scientists, researchers, advanced students and clinicians working in stem cells, regenerative medicine or tissue engineering.